Lighting for digital photography from snapshots to great shots / Syl Arena ; penerjemah Nadya Adwiani ; penyunting Sri Noor Verawaty. - SYL ARENA; Nadya Adwiani; Sri Noor Verawaty (Prigel, 2014)
ix, 299 hlm. : ilus. ; 25 cm [3 eks.]